Managing Government Digital Reputation through Big Data Processing - Khoirun Nisa'; Effy Rusfian; Zaenab Zaenab (Magister Ilmu Administrasi Publik, 2018)
The objective of this paper is to assess government reputation management performance by lev-eraging Big Data technology, internet, and public relations capacity, in particular creating credible information for the public. The research used a case study methodology on Indonesi-aBaik.id management for the period between 13th September to 13th October, 2017. The focus of the research was on the degree to which big data processing influenced communication, pub-lic persuasion, and content. Research techniques used to collect data including in-depth inter-views, observation, and literature review through elated techniques. Research findings indicate that effective Big Data processing is underpinned by quality data analysis and creative content development skills. This research contributes to knowledge on the application of online reputa-tion management processes for public relations officials and general readers based on the four steps of management process by Cutlip as applied to reputation management analysis using Big Data technology effectiveness. Based on the result of the research the government reputation management practice should also followed by higher competence of the public relation officials especially on the skill of reputation management process and public persuasion skill, thus, the process of creating credible information can be done adequately.